Differences in Root Nitrogen Uptake Between Tropical Lowland Rainforests and Oil Palm Plantations - Edy, Nur; Yelianti, Upik; Irawan, Bambang; Polle, Andrea; Pena, Rodica (Frontiers in Plant Science, 2020)
Conversion of lowland tropical rainforests to intensely fertilised agricultural land-use systems such as oil palm (Elaeis guineensis) plantations leads to changes in nitrogen (N) cycling. Although soil microbial-driven N dynamics has been largely studied, the role of the plant as a major component in N uptake has rarely been considered. We address this gap by comparing the root N contents and uptake in lowland rainforests with that in oil palm plantations on Sumatra, Indonesia. To this aim, we applied 15N-labelled ammonium to intact soil, measured the 15N recovery in soil and roots, and calculated the root relative N uptake efficiency for ten days after label application. We found that root N contents were by one third higher in the rainforest than oil palm plantations. However, 15N uptake efficiency was similar in the two systems. This finding suggests that lower N contents in oil palm roots were likely caused by plant internal utilisation of the absorbed N (e.g., N export to fruit bunches) than by lower ability to take up N from the soil. 15N recovery in roots was primarily driven by the amount of root biomass, which was higher in oil palm plantation than rainforest. The oil palms unveiled a high capacity to acquire N, offering the possibility of enhancing sustainable plantation management by reduced N fertiliser application.